Iron removal in produced water using Lysinibacillus sphaericus and the bioflocculant effect (2018)
"Produced water is an important waste stream associated with the oil and gas industries. The aim of this study was to investigate the use of immobilized Lysinibacillus sphaericus (a microorganism with the capacity to metabolize hydrocarbons and perform metal adsorption) in a biological aerated filter (BAF) to treat oil-field produced water with iron excess (50 mg L-1). Iron siderophores were amplified for most of the strains of L. sphaericus tested. Preliminary tests showed an iron removal concentration in the effluent of less than 5 mg L-1 and kinetic of sorption adjusted to pseudo second order..."--Chapter 1.